Geographical Indication (GI) as a means of craft tourism: a case of muga silk in Assam, India - Das, Niranjan (Revista Brasileira de Ecoturismo (RBEcotur), 2022)
Geographical Indications (GI) is one of the tools of Intellectual Property Rights (IPR) that protects name of a good as originating in the territory of a WTO member country, a region or locality in that territory, where a given quality, reputation or other characteristics of the good is essentially attributable to its geographical origin. Muga Silk has been and continues to be an integral part of Assamese life and tradition. Assam is literally a ‘Silk country’ and silk culture is deep-rooted in the rural life and culture of Assamese people where Muga silk (Antheraea assamensis) is grown. There are 100 per cent of India’s Muga silk production is originated in Assam and hence Assam silk occupies a unique position in the sericulture map of the world. Considering the ecological conditions, food plant distribution, presence of eco-types and species of diverse nature in co-existence, it is speculated that this region is home of origin of Muga (Antheraea assamensis). Muga cloth has 85.8 per cent absorption capacity of ultra-violet ray of sunlight. Muga, the unique golden-yellow silk of Assam was granted the Geographical Indication (GI) registration in 2007. The present research will be highlighted the geo-environmental condition, craft tourism prospect of Muga silk as well as its contribution on livelihood generation in the Brahmaputra valley of Assam. This paper tries to emphasize the possibility of craft tourism in Muga rearing areas of Assam, so that the host community might earn their livelihood from tourism activity.